Fungal palaeodiversity revealed using high‐throughput metabarcoding of ancient DNA from arctic permafrost. (22nd November 2012) - Bellemain, Eva; Davey, Marie L.; Kauserud, Håvard; Epp, Laura S.; Boessenkool, Sanne; Coissac, Eric; Geml, Jozsef; Edwards, Mary; Willerslev, Eske; Gussarova, Galina; Taberlet, Pierre; Brochmann, Christian
Summary The taxonomic and ecological diversity of ancient fungal communities was assessed by combining next generation sequencing and metabarcoding of DNA preserved in permafrost. Twenty‐six sediment samples dated 16 000–32 000 radiocarbon years old from two localities in Siberia were analysed for fungal ITS. We detected 75 fungal OTUs from 21 orders representing three phyla, although rarefaction analyses suggested that the full diversity was not recovered despite generating an average of 6677 ± 3811 (mean ± SD) sequences per sample and that preservation bias likely has considerable effect on the recovered DNA. Most OTUs (75.4%) represented ascomycetes. Due to insufficient sequencing depth, DNA degradation and putative preservation biases in our samples, the recovered taxa probably do not represent the complete historic fungal community, and it is difficult to determine whether the fungal communities varied geographically or experienced a composition shift within the period of 16 000–32 000 bp. However, annotation of OTUs to functional ecological groups provided a wealth of information on the historic communities. About one‐third of the OTUs are presumed plant‐associates (pathogens, saprotrophs and endophytes) typical of graminoid‐ and forb‐rich habitats. We also detected putative insect pathogens, coprophiles and keratinophiles likely associated with ancient insect and herbivore faunas. The detection of putative insect pathogens, mycoparasites, aquatic fungi and endophytes broadens our previous knowledge of the diversity of fungi present in Beringian palaeoecosystems. A large group of putatively psychrophilic/psychrotolerant fungi was also detected, most likely representing a modern, metabolically active fungal community.